Expertise and Skills Acquisition. - Staszewski, James J. (Taylor & Francis, 2013)
The research on human expertise and complex skill acquisition that Wlliam G. Chase performed in the decade between publication of the classic chess studies he conducted with Herb Simon in 1973 and his untimely and tragic death has proven profoundly influential and enduring. Its impact spans disciplines that include Psychology, Computer Science, Education, Cognitive Neuroscience, Medicine, and Human Factors. It has contributed significantly to the emergence of Cognitive Engineering and has led to significant applications in the areas of training and instruction and knowledge-based ""intellig.